Inclusive Statistics : Human Development and Disability Indicators in Low- and Middle-Income Countries - Mitra, Sophie; Yap, Jaclyn; Herve, Justine; Chen, Wei (World Bank, Washington, DC, 2021)
This paper disaggregates human development indicators across disability status to assess the situation of persons and households with disabilities. The paper uses 24 censuses and general household surveys from 21 low- and middle-income countries. Disability status is measured through self-reports of functional difficulties (for example, seeing or hearing). There are several findings of interest. First, disability is not rare in low- and middle-income countries. The median prevalence stands at 10 percent among adults ages 15 and older, and at 23 percent among households. There are consistent inequalities associated with disability and, in particular, with respect to educational attainment, work outcomes, poverty, food security, exposure to shocks, living conditions, and assets. At the same time, not all persons with functional difficulties experience deprivations. There is a gradient in inequalities associated with the degree of functional difficulty: persons with at least a lot of difficulty tend to be worse off than persons with some difficulty, who themselves tend to be worse off than persons with no difficulty. The results in this paper on the prevalence of functional difficulties and their association with socioeconomic deprivations show that disability should be central to human development policy, data, and research. More work is needed to curb the inequalities associated with disability.